2005
DOI: 10.1186/1476-0711-4-20
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of Eugenol and Cinnamaldehyde against the human gastric pathogen Helicobacter pylori

Abstract: Background: Eradication of Helicobacter pylori is an important objective in overcoming gastric diseases. Many regimens are currently available but none of them could achieve 100% success in eradication. Eugenol and cinnamaldehyde that are commonly used in various food preparations are known to possess antimicrobial activity against a wide spectrum of bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(115 citation statements)
references
References 28 publications
4
101
0
3
Order By: Relevance
“…It has been shown that cinnamaldehyde is effective against a variety of bacteria, viruses and fungi. 60 Cinnamaldehyde exhibited the MIC values of 0.1–0.5 μg/mL against E. coli (0.1 μg/mL), B. subtilis (0.5 μg/mL) and MRSA (0.25 μg/mL). Cinnamaldehyde inhibited the GTPase activity thus inhibiting the assembly of FtsZ protofilaments.…”
Section: Ftsz Inhibitorsmentioning
confidence: 97%
“…It has been shown that cinnamaldehyde is effective against a variety of bacteria, viruses and fungi. 60 Cinnamaldehyde exhibited the MIC values of 0.1–0.5 μg/mL against E. coli (0.1 μg/mL), B. subtilis (0.5 μg/mL) and MRSA (0.25 μg/mL). Cinnamaldehyde inhibited the GTPase activity thus inhibiting the assembly of FtsZ protofilaments.…”
Section: Ftsz Inhibitorsmentioning
confidence: 97%
“…14,15 Common medicinal plants used by local populations include Ocimum gratissimum , whose essential oil and main constituent eugenol displays anthelmintic and antimicrobial activities, 16,17 and Lippia sidoides , which is rich in the general antiseptic thymol. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Further, H. pylori did not develop any resistance towards these compounds even after 10 passages grown at sub-inhibitory concentrations. These results indicate that eugenol and cinnamaldehyde may prevent H. pylori growth in vitro, without acquiring any resistance [133].…”
Section: Antimicrobial Activity: Mode Of Actionmentioning
confidence: 76%
“…The suggested mechanism of inhibition of energy generation is inhibition of glucose uptake or its utilization and effects on membrane permeability [89]. Ali et al [133] studied the antimicrobial activities of eugenol and cinnamaldehyde against the human gastric pathogen Helicobacter pylori [133]. Both eugenol and cinnamaldehyde inhibited the growth of all the 30 H. pylori strains tested, at a concentration of 2 mg/ml, at 9 and 12 h of incubation, respectively.…”
Section: Antimicrobial Activity: Mode Of Actionmentioning
confidence: 99%